2020
DOI: 10.1038/s41438-020-00340-x
|View full text |Cite
|
Sign up to set email alerts
|

Decoding altitude-activated regulatory mechanisms occurring during apple peel ripening

Abstract: Apple (Malus domestica Borkh) is an important fruit crop cultivated in a broad range of environmental conditions. Apple fruit ripening is a physiological process, whose molecular regulatory network response to different environments is still not sufficiently investigated and this is particularly true of the peel tissue. In this study, the influence of environmental conditions associated with low (20 m) and high (750 m) altitude on peel tissue ripening was assessed by physiological measurements combined with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 53 publications
(95 reference statements)
2
31
0
Order By: Relevance
“…Anthocyanin pigment is responsible for Crimson seedless table grape berry coloration. This pigment is negatively affected by climate and differences between day and night temperature during the veraison stage [5] and it is also affected by the low altitude [6,7]. Various reasons for inferior color development in table grapes have been reported for the conditions prevalent in Egypt, such as high temperature [8,9]) and vigorous growth with dense, shaded canopies [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanin pigment is responsible for Crimson seedless table grape berry coloration. This pigment is negatively affected by climate and differences between day and night temperature during the veraison stage [5] and it is also affected by the low altitude [6,7]. Various reasons for inferior color development in table grapes have been reported for the conditions prevalent in Egypt, such as high temperature [8,9]) and vigorous growth with dense, shaded canopies [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The highest contents of total phenolic compounds, total flavonoids and total flavonols were found in the fruits from locations at the highest altitude (Mukhawa, 2780 m) than those from locations at lower altitudes [41]. A recently published research showed that variation in altitudeinduced changes in multiple biochemical pathways in apple peels of the cultivar 'Fujiku' during the fruit ripening [42]. Phenolic compounds of all the groups were increased at high altitude (750 m) compared to low altitude (20 m) accompanied by elevated expression of some key enzymes involved in the biosynthesis of these compounds.…”
Section: Tablementioning
confidence: 97%
“…It depends on the presence (climacteric) or absence (non-climacteric) of rise in respiration and ethylene production [2]. Ethylene coordinates the ripening process but is also known to regulate gene expression on several stages of fruit development [4][5][6]. The transduction pathway initiates when ethylene binds to a specific receptor, that will initiate the signaling cascade by releasing CTR1 and EIN2 binding, activating several transcription factors (EIN3/EIL1 and ERFs).…”
Section: Introductionmentioning
confidence: 99%
“…The transduction pathway initiates when ethylene binds to a specific receptor, that will initiate the signaling cascade by releasing CTR1 and EIN2 binding, activating several transcription factors (EIN3/EIL1 and ERFs). These transcription factors regulate genes underlying ripening-related traits, such as pulp firmness [2][3][4][5][6]. Ethylene exogenous treatment rapidly increases the transcription of 2 of 19 all these genes regulated by this hormone [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation